HERSCHEL-ATLAS: A BINARY HyLIRG PINPOINTING A CLUSTER OF STARBURSTING PROTOELLIPTICALS - Ivison, R; Swinbank, A; Smail, I; Harris, A; Bussmann, R; Cooray, A; Cox, P; Fu, H; Kovacs, A; Krips, M; Narayanan, D; Negrello, M; et al. (2013)
Panchromatic observations of the best candidate hyperluminous infrared galaxies from the widest Herschel extragalactic imaging survey have led to the discovery of at least four intrinsically luminous z = 2.41 galaxies across an ≈100 kpc region - a cluster of starbursting protoellipticals. Via subarcsecond interferometric imaging we have measured accurate gas and star formation surface densities. The two brightest galaxies span ∼3 kpc FWHM in submillimeter/radio continuum and CO J = 4-3, and double that in CO J = 1-0. The broad CO line is due partly to the multitude of constituent galaxies and partly to large rotational velocities in two counter-rotating gas disks - a scenario predicted to lead to the most intense starbursts, which will therefore come in pairs. The disks have M dyn of several × 1011 M o, and gas fractions of ∼40%. Velocity dispersions are modest so the disks are unstable, potentially on scales commensurate with their radii: these galaxies are undergoing extreme bursts of star formation, not confined to their nuclei, at close to the Eddington limit. Their specific star formation rates place them ≳ 5 × above the main sequence, which supposedly comprises large gas disks like these. Their high star formation efficiencies are difficult to reconcile with a simple volumetric star formation law. N-body and dark matter simulations suggest that this system is the progenitor of a B(inary)-type ≈1014.6- o cluster. © 2013. The American Astronomical Society. All rights reserved.